Foliar architecture and physio-biochemical plasticity determines survival of Typha domingensis pers. Ecotypes in nickel and salt affected soil. (1st October 2021) - Akhter, Noreen; Aqeel, Muhammad; Hameed, Mansoor; Sakit Alhaithloul, Haifa Abdulaziz; Alghanem, Suliman Mohammed; Shahnaz, Muhammad Muslim; Hashem, Mohamed; Alamri, Saad; Khalid, Noreen; Al-zoubi, Omar Mahmoud; Iqbal, Muhammad Faisal; Masood, Tayyaba; et al.
Abstract: Six ecotypes of Typha domingensis Pers. Jahlar (E1 ), Sheikhupura (E2 ), Sahianwala (E3 ), Gatwala (E4 ), Treemu (E5 ) and Knotti (E6 ) from different ecological regions were collected to evaluate the leaf anatomical and biochemical attributes under different levels of salinity and nickel stress viz ; L0 (control), L1 (100 mM + 50 mg kg −1 ), L2 (200 mM + 100 mg kg −1 ) and L3 (300 mM + 150 mg kg −1 ). Presence of salt and Ni in rooting medium consistently affected growth, anatomical and physio-biochemical attributes in all Typha ecotypes. Discrete anatomical modifications among ecotypes such as reduced leaf thickness, increased parenchyma area, metaxylem cell area, aerenchyma formation and improved metaxylem vessels were recorded with increasing dose of salt and Ni. The minimum anatomical damages were recorded in E1 and E6 ecotypes. In all ecotypes, progressive perturbations in ionic homeostasis (Na +, K +, Cl −, N) due to salt and metal toxicity were evident along with reduction in photosynthetic pigments. Maximum enhancement in Catalase (CAT), Superoxide dismutase (SOD), Peroxidase (POD) and modulated Malondialdehyde (MDA) activity was recorded in E1 and E6 as compared to other ecotypes. Accumulation of large amounts of metabolites such as total soluble sugars, total free amino acids content in Jahlar, Knotti, Treemu and Sahianawala ecotypes under different levels of salt and Ni prevented cellular damages in T. domingensis Pers. The correlation analysis exhibited a close relationship among different levels of salinity and Ni with various plant attributes. PCA-Biplot verified our correlational analysis among various attributes of Typha ecotypes. An obvious separation of Typha characters in response to different salinity and Ni levels was exhibited by PC1. We recommend that genetic potential of T. domingensis Pers. To grow under salt and Ni stresses must be investigated and used for phytoremediation and reclamation of contaminated soil. Graphical abstract: Image 1 Highlights: Nickel and salt toxicity significantly affect plant survival and adaptation capacity. Leaf architecture with metabolic adjustments are essential for ecological success. Growth and physio-biochemical attributes in Typha ecotypes showed differential ability to respond polluted soil. PCA-Biplot verified correlation among various attributes of Typha ecotypes.